Treating the troponin: adverse consequences of over-treatment of elevated troponin in non-coronary presentations. Issue 1 (February 2019) - Morrow, A; Ahmad, F; Steele, C; McEntegart, M; Murdoch, D
Background and aims: Anti-platelet and anti-thrombotic therapy are well-established treatments in acute coronary syndromes. Highly sensitive assays have diminished the positive predictive value of troponin in acute coronary syndromes and increased the importance of the clinical assessment in interpreting positive results. This cohort study sought to investigate over-treatment of non-coronary troponin rises and associated adverse outcomes. Methods and results: We reviewed 223 consecutive patients presenting to Queen Elizabeth University Hospital, Glasgow, with suspected acute coronary syndromes over a six-week period. Of these, 27 (12%) met our 'inappropriate therapy' criteria. This group had a low ischaemic risk (HEART score: 4.2 ± 1.4) (GRACE score: 117 ± 30.8) but an intermediate-high bleeding risk (CRUSADE score: 34 ± 14.5). Approximately half of the patients (14/27, 52%) reported chest pain, with only 4/27 (15%) having ischaemic ECG changes. There were three intracranial haemorrhages, each after the patient had received a single dose of aspirin, ticagrelor and fondaparinux. Conclusion: The combination of injudicious high-sensitivity troponin testing with potent anti-platelet and anti-thrombotic therapy was associated with possible over-treatment of patients and associated harm. Emphasis on interpretation of troponin in the context of clinical presentation and improved awareness of type 2 myocardial infarction are essential to limit iatrogenic pharmacological harm.